On the link between Barents‐Kara sea ice variability and European blocking. Issue 10 (31st May 2016) - Ruggieri, P.; Buizza, R.; Visconti, G.
Abstract: This study examines the connection between the variability of sea ice concentration in the Barents and Kara (B‐K) seas and winter European weather on an intraseasonal time scale. Low sea ice regimes in autumn and early winter over the B‐K seas are shown to affect the strength and position of the polar vortex, and increase the frequency of blocking regimes over the Euro‐Atlantic sector in late winter. A hypothesis is presented on the mechanism that links sea ice over the B‐K seas and circulation regimes in the North Atlantic, and is investigated considering 34 years of European Centre for Medium‐Range Weather Forecasts reanalysis data. Four key steps have been identified, starting from a local response of the near‐surface fluxes and modification of the upper tropospheric wave pattern, to the stratospheric adjustment and the tropospheric response in the North Atlantic. The proposed mechanism explains the delayed, late winter response of the North Atlantic Oscillation to the late autumn sea ice reduction, which has been found both in observations and model experiments. It also provides valuable insights on how the reduction of Arctic sea ice can influence the position of the tropospheric jet in the Euro‐Atlantic sector. Key Points: Impact of sea ice reduction on midlatitude weather Troposphere‐Stratosphere interaction